Impact of body mass index and polycystic ovary syndrome (PCOS) subtypes on periodontal health in Chinese women with PCOS and periodontitis - Xiaodan Liu; Fengran Wang; Xiao Wang; Qingxian Luan (Taylor & Francis Group, 2024)
Background This study aimed to investigate the impact of body mass index (BMI) and Polycystic Ovary Syndrome (PCOS) subtypes on periodontal parameters in Chinese women with PCOS and periodontitis.Method We conducted a retrospective case-control study analyzing data from 88 women with PCOS and 82 healthy controls. Participants were categorized by BMI (<24.0 kg/m2and ≥24.0 kg/m2) and PCOS subtypes. We compared periodontal parameters [including probing depth (PD), gingival bleeding index (GBI)] and reproductive hormone-related parameters.Results Women with PCOS and periodontitis had a significantly higher GBI (2.71 ± 0.53) compared to controls (2.25 ± 0.41, p < 0.0001). Among patients with BMI <24.0 kg/m2, those with PCOS had a younger age [25.00(5.00) vs. 26.00(6.00) years, p < 0.05], lower PD [3.24(0.55) mm vs. 3.43 (0.48) mm, p < 0.01], and higher GBI [2.63(0.76) vs. 2.23(0.55), p < 0.0001]. For BMI ≥24.0 kg/m2, PCOS patients had a higher GBI [2.91(0.36) vs. 2.38(0.59), p < 0.01] but a lower percentage of severe periodontal disease (p < 0.05).Conclusion PCOS could potentially worsen gingival inflammation among women already suffering from periodontitis, and a higher BMI might further intensify this correlation.